Development of a cell-line model to mimic the pro-survival effect of nurse-like cells in chronic lymphocytic leukemia. Issue 1 (2nd January 2021) - Mohammad, Ishaque S.; Lin, Ke; Oates, Melanie; Khan, Umair T.; Burger, Jan; Pettitt, Andrew R.; Zhuang, Jianguo
Abstract: The interaction between Chronic lymphocytic leukemia (CLL) cells and monocyte-derived nurse-like cells (NLCs) is fundamentally important to CLL biology. However, studies of how CLL cells and NLCs interact have been hampered by the need for freshly obtained CLL blood samples, coupled with wide variation in the number of monocytes present in the blood of individual patients. Here, we report the development and validation of a cell-line model of NLCs which overcomes these difficulties. Co-culture of primary CLL cells with THP-1 cells induced to differentiate into macrophages by phorbol 12-myristate 13-acetate (PMA) significantly reduced both spontaneous and fludarabine-induced cell death of leukemic cells. Furthermore, compared with their M1-polarized counterparts, M2-polarized macrophages derived from PMA-differentiated THP-1 cells conferred to CLL cells greater protection from spontaneous and fludarabine-induced apoptosis. Since NLCs resemble M2 tumor-associated macrophages, this cell-line model could be useful for investigating the mechanisms through which NLCs protect CLL cells from spontaneous and drug-induced apoptosis.